Metabolic syndrome risk after gestational diabetes: a systematic review and meta-analysis. - Yuhong Xu; Shutong Shen; Lizhou Sun; Haiwei Yang; Bai Jin; Xiaohui Cao (PLoS ONE)
Background A number of studies have been conducted to investigate the risk of metabolic syndrome (MS) after gestational diabetes mellitus (GDM), but the results are contradictory. Accordingly, we performed a systematic review and meta-analysis to assess the association between these two conditions. The aim was to better understand the risks of MS with prior gestational diabetes. Methods Pubmed, ISI Web of Science, and Cochrane databases from September 1, 1979 to July 11, 2013 were searched to identify relevant studies. 17 studies containing 5832 women and 1149 MS events were included. We calculated the odds ratio (OR) with 95% confidence interval (CI) in analysis for each study using a random-effect or fixed-effect model. We also determined heterogeneity among these 17 articles and their publication bias. Results Women with a history of gestational diabetes had a significantly higher risk of MS than those who had a normal pregnancy (OR, 3.96; 95% CI, 2.99 to 5.26), but had significant heterogeneity (I (2) = 52.6%). The effect remained robust (OR, 4.54; 95% CI, 3.78-5.46) in the subgroup of Caucasians, but no association (OR, 1.28; 95% CI, 0.64-2.56) was found in Asians. Heterogeneity was reduced (body mass index (BMI) matched group I (2) = 14.2%, BMI higher in the GDM group I (2) = 13.2%) in the subgroup of BMI. In addition, mothers with higher BMI in the GDM group had higher risk of MS than those in the BMI matched group (BMI higher in GDM group OR, 5.39; 95% CI, 4.47-6.50, BMI matched group OR, 2.53; 95% CI, 1.88-3.41). Conclusions This meta-analysis demonstrated increased risk of MS after gestational diabetes. Therefore, attention should be given to preventing or delaying the onset of MS in GDM mothers, particularly in Caucasian and obese mothers.